PENYULUHAN ANTI KORUPSI SEJAK DINI PADA ANAK-ANAKDUSUNBABADAN,SELOMIRAH, NGABLAK,MAGELANG, JAWA TENGAH - Mellisa Fitri Ardtiyani (Asian Journal of Innovation and Entrepreneurship, 2014)
Corruption is familiar to the peoplenowadays. Themassive impact needa goodsystem that proper prevention against it.One thing you can do is to do counseling aboutthe dangers of corruption early on. Children, especially children in theBabadanvillagestill have the opportunity to be able to forman anti-corruption character.Therefore,education about anti-corruption programs need to be done in order to provideeducation about corruption and its dangers, as well as prevent the occurrence ofcorruption early on. Material submitted by various methods make the children is easyand happy whenreceiving the material.